2021
DOI: 10.1038/s41420-021-00757-w
|View full text |Cite
|
Sign up to set email alerts
|

Receptor interacting protein 3 kinase, not 1 kinase, through MLKL-mediated necroptosis is involved in UVA-induced corneal endothelium cell death

Abstract: Ultraviolet (UV) is one of the most energetic radiations in the solar spectrum that can result in various tissue injury disorders. Previous studies demonstrated that UVA, which represents 95% of incident photovoltaic radiation, induces corneal endothelial cells (CECs) death. Programmed cell death (PCD) has been implicated in numerous ophthalmologic diseases. Here, we investigated receptor-interacting protein 3 kinase (RIPK3), a key signaling molecule of PCD, in UVA-induced injury using a short-term corneal end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, previous data showed that RIPK3 transcripts is increased in NHDF treated by chronic UVB doses [32], making RIPK3 a protein of interest in the study of cell response to UVB. RIPK3, through MLKL-mediated necroptosis, was found to be involved in UVA-induced retina and cornea cell death [33,34]. Those results led us to investigate the involvement of RIPK3 and MLKL in UVBinduced cell death in NHDF.…”
Section: Introductionmentioning
confidence: 94%
“…However, previous data showed that RIPK3 transcripts is increased in NHDF treated by chronic UVB doses [32], making RIPK3 a protein of interest in the study of cell response to UVB. RIPK3, through MLKL-mediated necroptosis, was found to be involved in UVA-induced retina and cornea cell death [33,34]. Those results led us to investigate the involvement of RIPK3 and MLKL in UVBinduced cell death in NHDF.…”
Section: Introductionmentioning
confidence: 94%
“…Over the past decade, different approaches in treating ocular-related diseases by gene silencing [ 141 , 142 , 143 ], drugs [ 144 , 145 , 146 ], and oxygenating technologies targeting particularly the wound-healing mechanism [ 147 , 148 ] have been explored. There has been some success, yet further research is warranted for novel treatments and cell-free EV based therapy is emerging as a promising approach because of its advantages over ongoing options in many diseases [ 135 , 139 , 149 , 150 ].…”
Section: Can We Utilize Extracellular Vesicles In Treatments Regiment...mentioning
confidence: 99%
“…Although there have been approaches focused on silencing genes associated with cancer and subsequent cessation of tumor growth and metastasis 156,[225][226][227] residual side effects Nanomedicine is a hot topic in biotechnology that is centered on developing nanocarriers for prophylactic, diagnostic, and therapeutic uses and is a field of science that revolutionized cancer diagnosis and treatment. Nanocarriers are nanosized particles (1-100 nm in diameter) intended to selectively transport anticancer drugs into the tumor site.…”
Section: Reviewmentioning
confidence: 99%
“…For example, liposomes, 219,220 proteins, 221 polymers, 222 hydrogels, 223 inorganic NPs, 224 and other nanocarriers, play a crucial role in the delivery of chemotherapeutic agents and other modulators to induce an effective treatment for cancer. Although there have been approaches focused on silencing genes associated with cancer and subsequent cessation of tumor growth and metastasis 156,225–227 residual side effects and multidrug resistance remain concerns, there remain concerns about the residual side effects and the development of multidrug resistance.…”
Section: Progress In Biomaterials For Drug Delivery and Cancer Therapymentioning
confidence: 99%